Evaluating performance of wet unencapsulated PEDOT trilayer actuators operating in air and water. Issue 1 (26th March 2019) - Ebrahimi Takalloo, Saeedeh; Fannir, Adelyne; Nguyen, Giao T M; Plesse, Cedric; Vidal, Frederic; Madden, John D W
Abstract: Ionically electroactive devices with no encapsulation dry out in air if a solvent-based electrolyte is used, and exchange ions in wet environments, both of which cause the performance of the device to vary over time. In this paper, we investigate the behavior of bare poly(3, 4-ethylenedioxythiophene) trilayer actuators both in intermittent use and continuous cycling in open air and in water, in order to understand how their response changes with time and solvent loss. Not surprisingly, the devices slow as solvent evaporates, but, unexpectedly, the active displacement increases until a large fraction of the solvent is gone. The electrolyte used in these 360 μ m thick devices is a 1 M solution of Bis(trifluoromethane)sulfonimide lithium salt (Li + TFSI − ) in propylene carbonate (PC). The trilayers lose all their solvent within 8 d, with ∼40% loss within a day, when stored in an environment with controlled temperature and relative humidity of (23 ± 2)°C and (50 ± 3)%, respectively. The devices' speeds slow as the PC evaporates from the device (staying within 10% of their initial value after losing ∼20% of its PC content). Intermittent testing shows displacement of the device actually increases until only ∼14% of the PC content remains which would take almost 4 d if the device is stored in the controlled conditions mentioned above. This is largely due to the reduction of thickness in the trilayers, which then leads to higher curvature. Cycling in open air or in water leads to immediate displacement decrease: dropping 60% over one hour cycling in air and over 12 min cycling in water-due to the reduction of charge transfer rate. Overall, for applications where speed is not critical and operation is only needed for a matter of hours or days, encapsulation may not necessary. We expect that encapsulation will be beneficial to maintain the intermittent operation of the device and to maintain speed for longer periods of use (beyond 4 d and 12 h, respectively in the case studied). Encapsulation should also allow a stable displacement amplitude over time.